Peran Digital Platform dalam Mendorong Kewirausahaan Halal pada Generasi Z - Miftahal Anjarsabda Wira Buana; Moh Ah Subhan ZA; Zarkia Al Hikmah (JES (Jurnal Ekonomi Syariah), 2026)
Digital transformation has changed the global entrepreneurial landscape, including the development of the halal economy, which is increasingly integrated with digital technology. On the other hand, Generation Z, as digital natives, has adaptive characteristics towards technology and a tendency to build flexible and value-based businesses (purpose-driven entrepreneurship). This study aims to analyze the role of digital platforms in encouraging halal entrepreneurship among Generation Z. Specifically, this study examines the influence of digital platform use on halal entrepreneurship interest and practice by considering the mediating role of trust and perceived usefulness, as well as the moderating role of religiosity and digital literacy. The study used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through a Likert-scale questionnaire distributed to Generation Z aged 18–27 who are involved in digital business activities or interested in halal entrepreneurship. The research variables were developed based on the integration of the Technology Acceptance Model and the Theory of Planned Behavior in the context of digital platform-based halal entrepreneurship. The results show that digital platforms have a positive and significant influence on halal entrepreneurship. Digital platforms act as enablers in opening market access, accelerators in accelerating business growth, and validators in building trust and strengthening halal branding. Furthermore, trust and perceived usefulness are proven to mediate the relationship between digital platform usage and halal entrepreneurship. This study also found that religiosity and digital literacy strengthen the influence of digital platforms on halal entrepreneurial behavior among Generation Z. This study contributes to the development of sharia-based digital entrepreneurship literature by offering an integrative model that connects digital technology, Islamic values, and entrepreneurial behavior of Generation Z. Practically, the research findings can be a reference for the government, digital platforms, and business actors in developing a more inclusive, adaptive, and sustainable halal entrepreneurship ecosystem in the digital economy era.